(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2019)
Networking is a branch of engineering that is dedicated to the study of digital communications. Network engineering is responsible for high impact projects through the design and configuration of specialized hardware and software, as well as the control and management of these technologies. This area of ​​telecommunications has been managed mainly by male personnel. Here we show that one of the reasons why this phenomenon occurs is because the focus and promotion of network technologies have been directed from the web portals to the male audience. When reviewing the websites of the main networking technology companies in Spain, it can be seen that the female figure, when it is not absent, is in the background or does not directly relate to the use of technology at an expert level, of equal way, it is observed that the language is always directed towards the male sex. This work can be an important piece in the process of deconstructing the masculinization of other techno-scientific branches, in which sexist biases still remain.